Indonesian prefix ter- - Ni Wayan Suastini; Kadek Apriliani (English, 2018)
This study deals with finding and describing the meaning and function of Indonesian prefix ter- in the investigation report. This study applied descriptive qualitative research to find out the data. The analysis was conducted by applying a theory proposed by Kridalaksana (2007) about prefix ter-. After investigating the data it was found that the prefix ter- can be used to form verb, adjective, and noun. The most frequent form found in the data is a verb. These words express different meaning, such as state of affair (stative) which does not involve any action, as found in the verb terletak (situated), accidental or uncontrolled action, such as the verb terkunci (locked), superlative adjective which provided superlative meaning on the adjective as found in adjective terakhir (the last) and also legal term such as tersangka (the suspect) which shows that prefix ter- can be used to form the actor who does the specific action which is related to the law.